2017
DOI: 10.4018/ijseims.2017010101
|View full text |Cite
|
Sign up to set email alerts
|

Tribological Behavior of Electroless Ni-P, Ni-P-W and Ni-P-Cu Coatings

Abstract: The present paper considers the comparative study of tribological characteristics of various electroless alloy coatings viz. Ni-P, Ni-P-W and Ni-P-Cu. The tribological behavior of these coatings depends on various parameters like load, speed, lubricant, chemical compositions and heat treatment temperature to a great extent. One of the main effects of heat treatment on these coatings is phosphide precipitation, which makes them suitable for anti-wear applications. The property of binary Ni-P can be further impr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 28 publications
(19 reference statements)
0
8
0
Order By: Relevance
“…Nonetheless, few studies additionally reported about the hardness and tribological performance of the coating. 5,7,9,[19][20][21][22] Balaraju and Rajam 5 obtained as-deposited hardness of Ni-P-Cu almost similar to Ni-P coating (444 HV) and the same increases almost two folds (819 HV) after heat treatment at 400 C for 1 h. The increase in hardness upon heating is caused by the precipitation of crystalline NiCu and Ni 3 P phases from the amorphous state. 23 Besides, the increase in Cu concentration in the coating brings about a reduction in its hardness.…”
Section: Introductionmentioning
confidence: 91%
See 2 more Smart Citations
“…Nonetheless, few studies additionally reported about the hardness and tribological performance of the coating. 5,7,9,[19][20][21][22] Balaraju and Rajam 5 obtained as-deposited hardness of Ni-P-Cu almost similar to Ni-P coating (444 HV) and the same increases almost two folds (819 HV) after heat treatment at 400 C for 1 h. The increase in hardness upon heating is caused by the precipitation of crystalline NiCu and Ni 3 P phases from the amorphous state. 23 Besides, the increase in Cu concentration in the coating brings about a reduction in its hardness.…”
Section: Introductionmentioning
confidence: 91%
“…21 Both adhesive and abrasive wear mechanisms are reported for Ni-P-Cu coatings. 22 Besides, the EN coating with high-range P content shows higher friction performances than low-and medium-range P concentrations. Similarly, the ternary Ni-P-W coating with high W shows better wear performance than the binary EN coating and low W content Ni-P-W coatings.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The FESEM micrographs of as-plated and heat-treated Coating-1 are shown in Figure 1. The heat treatment temperature and the amount of phosphorous content influence the phase structure of the coatings [33], leading to changes in its surface morphology. The as-plated coating reveals a cauliflower-like morphology, as seen in Figure 1a, which is also reported by several researchers [4,9].…”
Section: Microstructure Characterization and Composition Analysis (Edx)mentioning
confidence: 99%
“…4 However, heat treatment leads to several changes in its microstructure which have consequences on its hardness and tribological behavior. 5,6 Although heat treatment is vital for improving the strength of most of the EN coatings, few studies actually deal with the issues with heat treatment and their impact on the performance of the coatings. Tomlinson and Wilson 7 have studied the oxidation behavior of Ni–P and Ni–B coatings heat treated at higher temperature (i.e., 800°C and 1000°C for 440 min).…”
Section: Introductionmentioning
confidence: 99%